(untitled) (Research, Society and Development, 2022)
The Covid-19 pandemic was a world milestone that brought unexpected changes in people’s lives, being a sample of social isolation. Faced with reality, the objective of this study was to describe the productions that point out as psychological consequences of isolation during the Covid-19 pandemic as well as to verify the existence of actions that are minimized. For this, an integrative review of the literature was carried out in the Scientific Electronic Library Online database (Scielo.org) using the keywords: covid-19 X mental health X isolation. There were 11 articles in Portuguese selected and selected for the proposed objective and at the end of the study they were selected for the study corpus. In isolation isolation aces identified as following: depression, worry, stress fear of sadness, importance, abuse, abuse and drugs, isolation, drug abuse, isolation, sleep abuse, worry, worry and abuse of others. articles that may point to the need for interventions carried out to minimize the prevention of isolation such as possibilities for outdoor leisure and physical activities, relaxation, meditation, yoga, spirituality, regulated sleep and healthy eating day by day, interaction with family and friends through networks social media and recording one’s own emotions. In view of the results, we can see the need for measures to face the consequences of isolation and therapeutic intervention, especially in psychology, which was not perceived in the works, but which is believed to be one of the essential possibilities of problems of the analysis here.